Pemanfaatan Museum Mohammad Husni Thamrin sebagai Sumber Belajar Sejarah Siswa Kelas X di SMK Makarya 1 Jakarta Selatan - Novriyanto, Yus; Wibowo, Tubagus Umar Syarif Hadi; Rustamana, Agus (PGRI Kota Semarang, 2024)
The purpose of this study was to utilize the collections of the Mohammad Husni Thamrin Museum as a source of history learning for students. And to find out what obstacles are faced in utilizing the Mohammad Husni Thamrin Museum as a source of history learning for class X students of SMK Makarya 1 South Jakarta. With the research subjects from class X AK 1 and X AP 1 students. The method used is a qualitative approach. The collections at the Husni Thamrin Museum vary from photographs, paintings, dioramas, statues of warrior figures, documentary films, to Betawi art. For students, the museum is not only a source of history learning but also a place for learning history that can increase student learning motivation, increase analytical power to be able to realize their imagination of past events with evidence of historical sources in the museum. Some obstacles are such as time, distance, funds and school permits, which require preparation in designing learning in order to utilize the museum as a source of learning at school. Keywords: Museum, Utilization, Mohammad Husni Thamrin, History Learning Source.